Optimization design method for thickness of tool gasket of alkaline electrolytic cell
By designing reasonable tooling washer thickness and analysis methods, the problem of difficult to adjust the compression degree of the alkaline electrolytic cell electrode separator is solved, and the electrolytic reaction efficiency is improved and the assembly standards are unified.
Patent Information
- Application Number
- CN202411946894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art lacks the best assembly solution for alkaline electrolytic cells, which makes it difficult to adjust the compression degree of the electrode separator, affecting the electrolytic reaction efficiency, and excessive compression force may lead to rupture or short-circuiting of the separator.
By designing a reasonable tool washers thickness, using analytical means that comprehensively considers the electrode-diaphragm interface factors, calculate the actual axial force of the electrolytic cell to be measured, select an appropriate pressure range, perform a compression operation, screen out an acceptable gasket thickness range, and perform static ohmic value measurements through an electrochemical workstation to determine the optimal gasket thickness.
The contact environment between the electrode and the separator is effectively optimized, the interface resistance is reduced, the current conduction efficiency is improved, the alkali and water electrolytic reaction strength is significantly improved, and the assembly standards are unified, which improves the consistency and repeatability of assembly.
Smart Images

Figure CN119885613A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alkaline electrolytic cells, in particular to a thickness optimization design method for a tooling gasket of an alkaline electrolytic cell. Background Art
[0002] In the context of the current world energy structure dominated by fossil fuels, hydrogen energy is widely regarded as a strong competitor to reverse the energy situation due to its advantages such as high calorific value and zero emissions. Among its various main preparation methods, water electrolysis has become the research focus of various countries due to its clean and efficient advantages. Room-temperature water electrolysis hydrogen production technology is mainly divided into alkaline water electrolysis AWE operating at room temperature, proton exchange membrane water electrolysis PEM, and anion exchange membrane water electrolysis AEM according to the type of electrolyte. Among them, alkaline water electrolysis technology is the most mature, with the lowest cost and more economical, and is considered to be the main way to apply large-scale water electrolysis hydrogen production. The "sandwich" structure of cathode + diaphragm + anode is its main structural feature.
[0003] Among them, the degree of contact between the electrode and the diaphragm in the electrolysis chamber has a significant impact on the occurrence of the electrolysis reaction. A large number of literature and patents have studied this related problem and proposed corresponding solutions. Conventional electrolysis assembly experience believes that relatively tight assembly of diaphragms and electrodes can minimize ohmic impedance and thus enhance the reaction current. Therefore, the smallest possible axial compression distance will be selected to maximize the diaphragm-electrode interface contact. In the Chinese patent CN117926299A "A proton exchange membrane water electrolyzer and its assembly device and manufacturing method", a water electrolyzer assembly method proposed by Shanghai Jiaotong University and Shanghai Jian Hydrogen Energy uses a coil spring as a clamping device to achieve axial tightening of the electrode and diaphragm assembly to maximize interface contact. In addition, some existing laboratory electrolyzers use axial pressure modules to control the maximum interface contact. However, in actual operation, excessive compression force does not bring continuous positive gain to the reaction current, and sometimes even causes diaphragm rupture or even electrolyzer short circuit. In this regard, the team of Xiamen University's Tan Kah Kee Laboratory used microcurrent detection to observe the current transmission and material transfer effects near the contact interface of catalytic materials and other surfaces in the PEM electrolyzer. They found that interface distances that are too far or too close are not conducive to the transmission of current and materials, respectively, thereby causing poor electrochemical reactions. This indirectly illustrates that during the assembly of the electrolyzer, it is necessary to adjust the contact degree between the diaphragm and the electrode by controlling a reasonable range of compression force.
[0004] At present, there is no relevant research on the specific optimal assembly scheme for alkaline electrolyzers to adjust the compression degree of electrode diaphragms, and the most direct adjustment method is to control the support thickness of the polytetrafluoroethylene sealing gasket. Therefore, it is necessary to design a reasonable gasket thickness range test method. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a method for optimizing the thickness of the tooling gasket of the alkaline electrolytic cell. By comprehensively considering the electrode-diaphragm interface factors and introducing specific analysis methods, the development and application expansion of alkaline water electrolysis technology are effectively promoted and significant economic benefits are brought.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The present invention provides a method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell, comprising the following steps:
[0008] S1: Obtain the single bolt torque, bolt pitch, and number of bolts of the electrolytic cell, and calculate the actual axial force of the electrolytic cell to be tested;
[0009] S2: According to the axial force result obtained in S1, a clamping device with a corresponding pressure range is selected to perform a clamping operation on gasket-containing components of different thicknesses to obtain an acceptable gasket thickness range;
[0010] S3: Based on the acceptable gasket thickness range obtained in S2, the tooling is assembled in the actual electrolytic cell, and the static ohmic values at different thicknesses are obtained using an electrochemical workstation to obtain the optimal gasket thickness result.
[0011] Furthermore, in S1, the method for calculating the actual axial force of the electrolytic cell to be tested is:
[0012]
[0013] in:
[0014] F axis : Actual axial force of the electrolytic cell to be tested, unit N;
[0015] T: Single bolt torque, obtained according to the electrolyzer user manual provided by the manufacturer or actual operation conditions, unit: Nm;
[0016] p: bolt pitch, unit: mm;
[0017] n: number of bolts.
[0018] Furthermore, S2 includes the following specific steps:
[0019] Measure the thickness of the electrodes and membranes to be tested;
[0020] According to the thickness of the cathode and anode, adapt the PTFE gasket of equal thickness;
[0021] Select the thickness range of PTFE gasket for diaphragm;
[0022] Combine the electrode, the electrode-adapted PTFE, the diaphragm, and the diaphragm-adapted PTFE;
[0023] Based on the amount of compression during the test, the actual working thickness is determined;
[0024] Filter gasket thickness combinations to obtain gasket combination information that is within the acceptable range.
[0025] Further, in S2, the thickness of the electrode and membrane to be measured includes the thickness of the cathode and anode and the thickness of the diaphragm;
[0026] In S2, in the process of adapting polytetrafluoroethylene (PTFE) gaskets of equal thickness according to the thickness of the cathode and the anode: the shape of the gasket is consistent with the cross-sectional shape in the electrolytic cell and its internal flow field area can accommodate the electrode, and the shape of the PTFE gasket for the diaphragm is required to be consistent.
[0027] Furthermore, in S2, in the process of selecting the thickness range of the PTFE gasket for the diaphragm, the actually measured diaphragm thickness is used as the lower reference value of the thickness, the step length is 0.05 mm, and the setting is performed in sequence.
[0028] Furthermore, in S2, during the process of assembling the electrode, the electrode adapted to PTFE, the diaphragm, and the diaphragm adapted to PTFE, an empty electrolytic cell plate is used as a pressure piece each time to clamp the assembled parts therein and ensure that the relative positions are at the geometric center and will not slip.
[0029] Furthermore, in S2, the process of determining the actual working thickness based on the compression amount during the test includes: turning on the pressure instrument, fixing the axial pressure to the axial pressure calculated in S1, recording the relative position when the pressure head begins to contact the plate and the final stable position, obtaining the compression amount at this time, and thus determining the actual working thickness.
[0030] Furthermore, S3 specifically includes the following sub-steps:
[0031] Using the actual electrolytic cell to be tested, the gasket-electrode-diaphragm combinations within the acceptable gasket thickness range obtained in S2 are respectively installed in the actual cell;
[0032] Connect the electrochemical workstation to the electrolytic cell;
[0033] Using the electrochemical impedance spectroscopy function of the electrochemical workstation, static EIS measurements were performed on gasket-electrode-diaphragm combinations of different thicknesses under open circuit conditions;
[0034] The EIS curves under different thickness combinations were compared, and the thickness result with the smallest ohmic impedance was selected and determined as the optimal gasket thickness combination.
[0035] Furthermore, in S3, during the static EIS measurement, the working electrode and the SENSE are connected to the positive electrode, and the reference electrode and the counter electrode are connected to the negative electrode.
[0036] Furthermore, in S3, the specific process of determining the optimal gasket thickness combination includes: comparing the EIS curves under different thickness combinations, focusing on the part of the curve that reflects the ohmic impedance, intercepting the intersection of the curve and the horizontal axis in the impedance diagram to obtain the ohmic value of the entire electrolytic cell under this gasket thickness, and by comparing the ohmic values corresponding to each thickness combination, selecting the thickness result with the smallest ohmic impedance and determining it as the optimal gasket thickness combination.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1) The present invention fully considers the key effects of interfacial conductivity and material transport on the electrochemical reaction near the electrode-diaphragm interface. The contact environment between the electrode and the diaphragm is effectively optimized by designing a method for determining the thickness of the optimal gasket tooling. On the one hand, the precise selection of gasket thickness reduces the interface resistance, making the current conduction more efficient, thereby significantly improving the intensity of the alkaline water electrolysis reaction.
[0039] 2) In the previous alkaline electrolytic cell tooling fastening process, there was a lack of clear and unified gasket thickness selection standards, resulting in a large degree of arbitrariness in the assembly process and unstable product performance. The present invention successfully unified the assembly standards and determined the optimal gasket thickness for different electrolytic cells based on scientific and rigorous axial force calculations, compression tests, and electrochemical analysis processes. This standardized process greatly improves the consistency and repeatability of alkaline electrolytic cell assembly, ensuring that each electrolytic cell reaches a similar high performance level, whether in large-scale production or in the construction of small-scale experimental devices, effectively reducing quality problems and performance fluctuations caused by assembly differences.
[0040] 3) The present invention innovatively introduces electrochemical impedance and the degree of contact of the reaction interface as core analytical methods, opening up new research and development directions for the field of alkaline electrolyzer technology. This not only helps to deeply understand the complex electrochemical reaction mechanism of the electrode-diaphragm interface, but also provides a strong theoretical basis and practical guidance for the subsequent development of more advanced electrolyzer technology. Based on the present invention, researchers can further explore how to synergistically improve the performance of the electrolyzer by optimizing other related factors, such as developing new gasket materials, improving electrode structures, etc., thereby promoting the continuous innovation and expansion of the entire alkaline water electrolysis technology, playing a more important role in the field of new energy and adapting to the diversified application needs in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of the bolt torque and its equivalent axial force of the electrolytic cell;
[0042] Figure 2 This is a schematic diagram of the change of working thickness before and after compression;
[0043] Figure 3 Schematic diagram of the process for optimizing the thickness of tooling gaskets for alkaline electrolytic cells. DETAILED DESCRIPTION
[0044] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Component models, material names, connection structures, control methods, algorithms and other features not clearly described in this technical solution are all considered to be common technical features disclosed in the prior art.
[0045] Example 1
[0046] The optimal gasket tooling thickness design method for an alkaline electrolytic cell in this embodiment comprises the following steps:
[0047] 1) Calculation of the axial force of the electrolytic cell after actual measurement;
[0048] 2) According to the axial force result, a pressing device with a corresponding pressure range is selected to perform a pressing operation on gasket-containing components of different thicknesses to obtain an acceptable gasket thickness range;
[0049] 3) Based on the acceptable gasket thickness range results in 2), a real slot was used for tooling and an electrochemical workstation was used to obtain static ohmic values at different thicknesses to obtain the optimal gasket thickness result.
[0050] In order to simulate the pressure level of the electrolytic cell to be tested, it is necessary to obtain its actual axial pressure for the purpose of compression testing. Common laboratory-scale electrolytic cells usually use multiple extended bolts as axial fastening devices. The axial pressure calculation of the cell body can refer to the formula:
[0051]
[0052] F axis : Actual axial force of the electrolytic cell to be tested, unit N;
[0053] T: Single bolt torque, which can be obtained from the electrolyzer user manual provided by the manufacturer or actual operation conditions, in Nm;
[0054] p: bolt pitch, unit: mm;
[0055] n: number of bolts.
[0056] According to the calculated axial force results, a pressure instrument with a corresponding range is selected to carry out the tooling compression test. The pressure instrument needs to meet the requirements of being able to provide the real-time pressure value and absolute displacement at the pressure head at the same time. First, the thickness d of the electrode and membrane to be tested is measured. ec ,dea d d According to the thickness of the cathode and anode, a polytetrafluoroethylene (PTFE) gasket (hereinafter referred to as PTFE) of equal thickness is matched. The shape of the gasket must be consistent with the cross-sectional shape of the electrolytic cell and its internal flow field area must be able to accommodate the electrode. The shape of the PTFE gasket for the diaphragm must be consistent.
[0057] The thickness range of PTFE gasket for diaphragm should be selected based on the actual measured diaphragm thickness d d is the thickness reference value, the step length is 0.05mm, and they are superimposed one by one, that is, d d d d1 d d2 ……d dn (where d di =d d +i*0.05, the range of n can be determined according to the actual test results). Combine the electrode, electrode adapter PTFE, diaphragm, and diaphragm adapter PTFE. Use an empty electrolytic cell plate or a plate of the same material as a pressure piece each time, clamp the combined parts in it and ensure that the relative positions are in the geometric center and will not slip. Turn on the pressure instrument and fix the axial pressure to F axis , record the relative position when the pressure head starts to contact the plate and the final stable position, and obtain the compression amount Δd at this time i The actual working thickness at this time is d wi =d di +d c +d a -Δd i . Screening Δd i ≤6%×(d di +d c +d a ) gasket thickness combination, record the gasket combination within this range and prepare for the next round of ohm test after replacing the electrode and diaphragm.
[0058] Use the actual electrolytic cell to be tested, and install the gasket-electrode-diaphragm combination in the thickness range mentioned above, and connect the system liquid circuit. Use an electrochemical workstation to connect the electrolytic cell, using green and white (working electrode and SENSE) to connect the positive electrode, and yellow and red (reference electrode and counter electrode) to connect the negative electrode. Use the electrochemical impedance spectroscopy function to measure the actual static EIS in the open circuit state. Compare the EIS curves under different thickness combinations, and select the thickness result with the smallest ohmic impedance. Finally, the best gasket thickness combination is obtained.
[0059] like Figure 3As shown, in this embodiment, a method for designing the thickness of an optimal tooling gasket for an alkaline electrolytic cell is provided. Based on the experimental data of a new energy laboratory of a university, the above method is used to optimize the thickness of a PTFE gasket of an alkaline electrolytic cell, and specifically comprises the following steps:
[0060] Step 1: Obtain specific tank body fastening bolt parameters from the electrolytic cell manufacturer, including recommended fastening torque T and bolt pitch p, using the formula Calculate the equivalent axial pressure. The equivalent axial tightening force F is obtained by calculation. axis It is 9300N, so the stable pressure value of the electric pressure cylinder is selected as 9300N as the axial working pressure.
[0061] Step 2, select the double-sided nickel mesh and organic diaphragm as the working combination to be tested. According to the size data provided by the dealer, the nominal thickness of the nickel mesh and the diaphragm are 0.3mm and 0.5mm respectively. Select 2*2cm nickel mesh and 3*3 diaphragm as the working size. After net cutting, use a thickness gauge to measure and confirm that the size meets the above nominal thickness, and the superimposed thickness is confirmed to be 1.1mm. Since it was found in the preliminary experiment that the thickness of the nickel mesh electrode did not change during the direct application of axial pressure to the working combination, but the diaphragm would be embedded, compressed and deformed by the electrode, the thickness of the PTFE gasket for the diaphragm was used as a variable in the process of selecting the gasket thickness, thereby ensuring the singleness and axial symmetry of the variable. Based on 0.5mm (diaphragm thickness) as the benchmark, 0.6mm, 0.5mm, 0.4mm and 0.3mm were selected as the diaphragm gasket thickness, and 0.3mm gaskets were used for the nickel mesh electrodes on both sides. Use the electrolytic cell plate assembly without bolts as the pressurized component, clamp the electrode and its gasket, the diaphragm and its gasket into the two plates and turn on the press to clamp them to ensure that the parts are fixed in position. Then turn on the press press mode, and when the measured pressure value reaches 9300N, keep it for 1 minute. After 1 minute of constant pressure, reset the press, remove the working parts of the electrolytic cell, and note that the relative position of the electrode and the diaphragm must be kept unchanged at this time, and measure the total thickness of the electrode and the diaphragm.
[0062] Step 3: Based on the total thickness of the electrode and diaphragm under different diaphragm gasket thicknesses obtained in step 2, it is found that the working thickness changes of the three cases of diaphragm thickness of 0.3mm, 0.4mm and 0.5mm can all meet Δd i ≤6%×(d di +d c +d a) requirements, so these three diaphragm gasket thicknesses are screened for the next ohm test. Use the same electrode, diaphragm and its thickness as the test combination, install it into the measured electrolytic cell, and use a torque wrench to ensure that the bolt torque meets the test pressure. Connect it to the actual working alkali solution system and open the liquid circuit, connect the electrochemical workstation to the electrolytic cell pole ear, turn on the workstation after the liquid circuit runs for 1 minute, select the EIS mode, set the test voltage to open circuit voltage, the frequency range is 100000Hz to 0.1Hz, and start the test. After the test is completed, intercept the intersection of the curve and the horizontal axis in the impedance diagram to obtain the ohm value of the entire tank under this gasket thickness, and select the lowest result to obtain the optimal gasket thickness that meets the requirements.
[0063] According to the results shown in Table 1, 0.4 mm diaphragm gasket and 0.3 mm electrode gasket on both sides of the electrode were selected as the optimal tooling thickness of the electrolytic cell.
[0064] Table 1 Axial static compression and real slot ohm test results under different diaphragm gasket thickness
[0065]
[0066] In summary, the present invention not only takes into account the effects of interface conductivity and material transfer on the electrochemical reaction near the electrode-diaphragm interface on the original fastening of the electrolytic cell tooling, but also introduces electrochemical impedance and the degree of contact of the reaction interface as analysis methods, which can effectively improve the intensity of alkaline water electrolysis reaction, unify the assembly standards, provide technical support for the energy-saving development of alkaline water electrolysis technology, and increase economic benefits.
[0067] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell, characterized in that: The following steps are involved: S1: Obtain the single bolt torque, bolt pitch, and number of bolts of the electrolytic cell, and calculate the actual axial force of the electrolytic cell to be tested; S2: According to the axial force result obtained in S1, a clamping device with a corresponding pressure range is selected to perform a clamping operation on gasket-containing components of different thicknesses to obtain an acceptable gasket thickness range; S3: Based on the acceptable gasket thickness range obtained in S2, the tooling is assembled in the actual electrolytic cell, and the static ohmic values at different thicknesses are obtained using an electrochemical workstation to obtain the optimal gasket thickness result.
2. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 1, characterized in that: In S1, the method for calculating the actual axial force of the electrolytic cell to be tested is: in: F axis : Actual axial force of the electrolytic cell to be tested, unit N; T: Single bolt torque, obtained according to the electrolyzer user manual provided by the manufacturer or actual operation conditions, unit: Nm; p: bolt pitch, unit: mm; n: number of bolts.
3. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 1, characterized in that: S2 includes the following specific steps: Measure the thickness of the electrodes and membranes to be tested; According to the thickness of the cathode and anode, adapt the PTFE gasket of equal thickness; Select the thickness range of PTFE gasket for diaphragm; Combine the electrode, the electrode-adapted PTFE, the diaphragm, and the diaphragm-adapted PTFE; Based on the amount of compression during the test, the actual working thickness is determined; Filter gasket thickness combinations to obtain gasket combination information that is within the acceptable range.
4. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 3, characterized in that: In S2, the thickness of the electrodes and membranes to be measured includes the thickness of the cathode and anode and the thickness of the diaphragm; In S2, in the process of adapting polytetrafluoroethylene (PTFE) gaskets of equal thickness according to the thickness of the cathode and the anode: the shape of the gasket is consistent with the cross-sectional shape in the electrolytic cell and its internal flow field area can accommodate the electrode, and the shape of the PTFE gasket for the diaphragm is required to be consistent.
5. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 3, characterized in that: In S2, when selecting the thickness range of the PTFE gasket for the diaphragm, the measured diaphragm thickness is used as the lower thickness reference value, the step length is 0.05 mm, and the setting is performed in sequence.
6. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 3, characterized in that: In S2, during the process of assembling the electrode, the electrode adapted to PTFE, the diaphragm, and the diaphragm adapted to PTFE, an empty electrolytic cell plate is used as a pressure piece each time to clamp the assembled parts therein and ensure that the relative positions are at the geometric center and will not slip.
7. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 3, characterized in that: In S2, the process of determining the actual working thickness based on the compression during the test includes: turning on the pressure instrument, fixing the axial pressure to the axial pressure calculated in S1, recording the relative position when the pressure head begins to contact the plate and the final stable position, obtaining the compression at this time, and thus determining the actual working thickness.
8. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 1, characterized in that: S3 specifically includes the following sub-steps: Using the actual electrolytic cell to be tested, the gasket-electrode-diaphragm combinations within the acceptable gasket thickness range obtained in S2 are respectively installed in the actual cell; Connect the electrochemical workstation to the electrolytic cell; Using the electrochemical impedance spectroscopy function of the electrochemical workstation, static EIS measurements were performed on gasket-electrode-diaphragm combinations of different thicknesses under open circuit conditions; The EIS curves under different thickness combinations were compared, and the thickness result with the smallest ohmic impedance was selected and determined as the optimal gasket thickness combination.
9. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 1, characterized in that: In S3, during the static EIS measurement, the working electrode and SENSE are connected to the positive electrode, and the reference electrode and the counter electrode are connected to the negative electrode.
10. The method for optimizing the thickness of a tooling gasket of an alkaline electrolytic cell according to claim 1, characterized in that: In S3, the specific process of determining the best gasket thickness combination includes: comparing the EIS curves under different thickness combinations, focusing on the part of the curve that reflects the ohmic impedance, intercepting the intersection of the curve and the horizontal axis in the impedance diagram to obtain the ohmic value of the entire electrolytic cell under this gasket thickness, and by comparing the ohmic values corresponding to each thickness combination, selecting the thickness result with the smallest ohmic impedance and determining it as the best gasket thickness combination.
Citation Information
Patent Citations
Proton exchange membrane water electrolyser and assembling device and manufacturing method thereof
CN117926299A
Electrolytic bath and pre-tightening design method thereof
CN116575048A
Dynamic operation method for hydrogen production optimal working condition of electrolytic cell
CN118241254A
Electrolytic tank for producing hydrogen by electrolyzing water and equipment for producing hydrogen by electrolyzing water
CN218951510U
Electronic component attachment structure
JP2018019282A